2022
DOI: 10.1111/jgh.16017
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of efficacy and safety of potassium‐competitive acid blocker and proton pump inhibitor in gastric acid‐related diseases: A systematic review and meta‐analysis

Abstract: Background and Aim: Potassium-competitive acid blocker (PCAB) is a recent alternative to proton pump inhibitor (PPI) for potent acid suppression. The current systematic review and meta-analysis aimed to compare the efficacy and safety of PCAB versus PPI in treating gastric acid-related diseases. Methods: We searched up to June 5, 2022, for randomized controlled trials of gastric acid-related diseases that included erosive esophagitis, symptomatic gastroesophageal reflux disease (GERD), peptic ulcers, and Helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 41 publications
0
22
1
2
Order By: Relevance
“…Compared with PPI, vonoprazan has a more potent acid inhibition effect, and a favorable pharmacokinetic profile [34,35]. A previous meta-analysis showed that vonoprazan triple therapy achieved an eradication rate of greater than 90% and exceeded the eradication rate observed with PPI-based therapy [12,19]. However, the efficacy and safety profile of vonoprazan dual therapy compared with other treatments have not been well established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with PPI, vonoprazan has a more potent acid inhibition effect, and a favorable pharmacokinetic profile [34,35]. A previous meta-analysis showed that vonoprazan triple therapy achieved an eradication rate of greater than 90% and exceeded the eradication rate observed with PPI-based therapy [12,19]. However, the efficacy and safety profile of vonoprazan dual therapy compared with other treatments have not been well established.…”
Section: Discussionmentioning
confidence: 99%
“…In the Maastricht VI/Florence consensus report, vonoprazan in combination with antibiotics was also recommended as a first-line and second-line treatment, especially in patients with evidence of antimicrobial-resistant infections [18]. Vonoprazan triple therapy has demonstrated comparable or favorable efficacy and safety profiles compared to PPI-based triple therapy [19][20][21][22]. However, the efficacy and safety of vonoprazan dual therapy relative to vonoprazan triple therapy and PPI triple therapy are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Further, its elimination is independent from CYP2C19 metabolism, probably contributing to explain its greater effect[ 19 ]. A recent meta-analysis on 19 RCTs found that vonoprazan was superior to PPIs in healing erosive esophagitis, whereas there was no difference in the improvement of GERD symptoms[ 23 ]. However, evidence on refractory GERD is scarce, and more studies from Western countries are needed to expand knowledge on the effectiveness of this drug in the setting of erosive reflux disease.…”
Section: Question 12: Which Is the Role For P-cabs In Patients With G...mentioning
confidence: 99%
“…Takeda synthesized a new pyrrole derivative in 2010, 1‐[5‐(2‐fluorophenyl)‐1‐(pyridin‐3‐ ylsulfonyl)‐1 H ‐pyrrol‐3‐yl]‐ N ‐methylmethanamine monofumarate (TAK‐438 or vonoprazan fumarate), 115 that was a completely different formulation from other P‐CABs including SCH 28080 116 . In 2011 this drug was fully characterized and found to be K + ‐competitive, accumulated more effectively than SCH 28080 in parietal cells, had a slow disassociation rate and very high affinity for the H + , K + ‐ATPase pump, thus providing faster onset and longer‐lasting inhibition of acid secretion compared to SCH 28080 117 In many clinical trials, TAK‐438 has proven to be effective at maintaining a high night‐time pH with a good safety profile, 118–120 and is effective or superior to PPI treatment with a similar safety profile for treating ulcer diseases, erosive esophagitis, H. pylori infection, and GERD 121–123 . Greater acid suppression results in much higher levels of serum gastrin and the associated risks compared with PPIs 124 .…”
Section: Control Of Gastric Acid Secretion By Potassium‐competitive A...mentioning
confidence: 99%
“…116 In 2011 this drug was fully characterized and found to be K +competitive, accumulated more effectively than SCH 28080 in parietal cells, had a slow disassociation rate and very high affinity for the H + , K + -ATPase pump, thus providing faster onset and longer-lasting inhibition of acid secretion compared to SCH 28080 117 In many clinical trials, TAK-438 has proven to be effective at maintaining a high night-time pH with a good safety profile, [118][119][120] and is effective or superior to PPI treatment with a similar safety profile for treating ulcer diseases, erosive esophagitis, H. pylori infection, and GERD. [121][122][123] Greater acid suppression results in much higher levels of serum gastrin and the associated risks compared with PPIs. 124 Tegoprazan and fexuprazan are the latest generation of P-CABs, with similar efficacy profiles to TAK-438.…”
Section: Control Of Gastric Acid Secretion By Potassium-competitive A...mentioning
confidence: 99%